An analysis of students’ Grammar mastery in writing recount text - Ainun Nur Oktaviani Agustam; Kisman Salija; Ahmad Talib (International Journal of Humanities and Innovation (IJHI), 2022)
The present study aims to find out the students’ ability to write recount text and find out the students’ grammar mastery in writing recount text, and how the grammar errors that the students make relate to their recount text production. This research used mixed methods. A writing test was implemented as the instrument in this research. The population of this research was the tenth-grade students of one of the public senior high schools in Gowa regency, South Sulawesi, Indonesia. Thirty students were chosen randomly using a convenience sampling approach. The researchers found that the students could construct recount text well in analyzing the data. This research also showed that all the samples achieved the minimum completeness criteria that the school determines. The sample applied grammar in recount text, including simple past tense, past continuous tense, past perfect tense, past future tense, verb conjugation, and auxiliary verb. The students' recount text had grammatical problems. Intralingual errors caused most of the errors that showed in students' recount text. It occurs because students may lack experience and knowledge of English grammar, which differs from the grammar of their native tongue. As a result, students should enhance their writing skills and practice more, especially while producing recount texts